Evaluation of carcinogenic risk of PUVA versus Re-PUVA in psoriatic patients. Issue 2 (May 2017) - Mashaly, Heba M.; Hussein, Marwa F.; Hamdy, Shaimaa; Shaker, Olfat
Abstract : Introduction: Photochemotherapy (PUVA) is one of the classic treatment modalities for psoriasis. Adding retinoids in the form of Re-PUVA is hypothesized to reduce the possible carcinogenic potential of PUVA. 8-Oxoguanine (8-oxoG) is among the most mutagenic oxidative DNA modifications that induce replication errors. Objective: To evaluate the possible carcinogenic protective effect of adding retinoids to PUVA in psoriatic patients. Patients and methods: A prospective, randomized, controlled study was conducted that included 20 patients with psoriasis who were randomly divided into two groups: group A received PUVA therapy and group B received Re-PUVA therapy. Each of the 20 patients received 30 sessions of PUVA photochemotherapy. Patients of group B received additional oral retinoids 2 weeks before the start of PUVA sessions, which continued until the end of the PUVA sessions. Serum samples were taken from each of the 20 patients before and after the last PUVA session and were used to measure the 8-oxoG level. Results: A significant drop in Psoriasis Area Severity Index score was detected in both groups. However, onset of clinical response was significantly earlier in the Re-PUVA group ( P =0.037) together with significantly lower cumulative dose of UVA ( P =0.002). A rise in serum level of 8-oxoG was noticed in psoriasis patients following PUVA therapy. In contrast, a drop in serum level of 8-oxoG was noticed following Re-PUVA therapy. Comparing the change in serum levels of 8-oxoG in patients receiving PUVA with those in patients receiving Re-PUVA revealed a more significant drop in 8-oxoG in the latter group ( P =0.023). Conclusion: Re-PUVA was able to achieve the same clinical response as PUVA in psoriasis patients, but with an earlier onset of clinical response, lower UVA cumulative dose, less DNA damage in the serum, and hence a lower carcinogenic potential.